Studi Literatur: Berbagai Daun Tumbuhan Indonesia Sebagai Antidiabetes - Arini Salsabila Hasibuan; Dwika Ardelya Pratiwi; Maharani Br Barus; Salshabila Azzahra Sirait (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Diabetes, or hyperglycemia, is a chronic condition characterized by an increase in blood sugar in the body caused by the inability of the pancreas to produce insulin or the body's inability to use the insulin it produces effectively. In Indonesia, there are several plants that have beneficial effects on health. Traditionally, because of the many benefits and abundant content of leaves in nature, the use of leaves has been widely used by diabetics. The purpose of this literature review is to determine the anti-diabetic content of Indonesian plant leaves. The methodology used to write this article is based on a literature review approach. The journal collection process is based on the criteria specified in the literature research. The criteria for participation are journals created in the last 7 years and indexed on Google Scholar. Based on the results of a literature search, seven types of Indonesian plant leaves were found that had potential as anti-diabetes, namely hydrochloric acid leaves, bay leaves, cherry leaves, star fruit leaves, bay leaves, red betel leaves and mango. From the research outcome of this article, it was concluded that the use of Indonesian plant leaves can be an alternative recommendation for the treatment of diabetes.